2016
DOI: 10.17116/terarkh2016881257-61
|View full text |Cite
|
Sign up to set email alerts
|

The role of renal anemia and cardiovascular disease in the progression of chronic glomerulonephritis

Abstract: 1 Кафедра терапии общей практики с курсом семейной медицины Киргизской государственной медицинской академии им. И.К. ахун-баева, Бишкек, Киргизия;2 ГБоУ вПо «Российский национальный исследовательский медицинский университет им. Н.И. Пирогова», Москва, Россия Резюме Цель исследования. Изучить скорость прогрессирования хронического гломерулонефрита в условиях присоединения анемии и сердечно-сосудистых заболеваний (ссз). Материалы и методы. обследовали 231 пациента (133 мужчин и 98 женщин) с хроническим гломеруло… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…in the group of persons with a high content of MK plasma, the average value of Hb was 130.9 ± 27.1 g/L compared to 136.1 ± 24.9 g/L (group 2). The effect of Hb content on the rate of progression of nephropathy was established in a series of studies [14,15]. On the contrary, timely detection and treatment of anemia in CKD, especially in the predialysis stage, significantly improves prognosis, while reducing the connection of cardiovascular complications (MTR) [1,2,11].…”
Section: The Results Of the Study And Their Discussionmentioning
confidence: 99%
“…in the group of persons with a high content of MK plasma, the average value of Hb was 130.9 ± 27.1 g/L compared to 136.1 ± 24.9 g/L (group 2). The effect of Hb content on the rate of progression of nephropathy was established in a series of studies [14,15]. On the contrary, timely detection and treatment of anemia in CKD, especially in the predialysis stage, significantly improves prognosis, while reducing the connection of cardiovascular complications (MTR) [1,2,11].…”
Section: The Results Of the Study And Their Discussionmentioning
confidence: 99%
“…2,3 Moreover, a large number of studies have shown that anemia is an important factor affecting the occurrence and development of CVD, and too high or low hemoglobin (Hb) may increase the incidence of CVD and the risk of death in peritoneal dialysis (PD) patients. 4,5,6 In 2011, the "Dialysis Outcomes and Practice Pattern Study (DOPPS)" concluded that patients with greater Hb fluctuation had a higher risk of death. 7 A retrospective study by Taiwan scholars revealed that Hb fluctuation could not predict the prognosis of PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of death in patients with ERSD, accounting for approximately 50% of cases 2,3 . Moreover, a large number of studies have shown that anemia is an important factor affecting the occurrence and development of CVD, and too high or low hemoglobin (Hb) may increase the incidence of CVD and the risk of death in peritoneal dialysis (PD) patients 4,5,6 …”
Section: Introductionmentioning
confidence: 99%